Levitin–Polyak well-posedness of generalized bilevel equilibrium problem with perturbations. (2nd November 2021) - Virmani, Garima; Srivastava, Manjari
Abstract : In this paper, a new class of problem known as the generalized bilevel mixed equilibrium problem with perturbations (GBMEPP) has been introduced on a real Banach space. Based on the diameter and the measure of non-compactness of the approximate solution set of the above stated problem, criteria and characterizations have been derived for Levitin–Polyak (LP) well-posedness. A sufficient condition for the LP well-posedness has also been derived assuming the boundedness of the approximate solution set.